Investigating the acceptance of course file electronic knowledge acquisition PPPG (CEKAP) system via utaut model - Mohamad, Mastura; Mengen, Rozita; Mohd Azmi, Nor Farhana; Mohd Mokhtar, Noorsuraya; Md Juperi, Nurul Zahidah (Universiti Teknologi MARA, Kedah, 2023)
There is still a physical buildup of files in the process of collecting, recording and documenting files in an organization, which can slow down the search for files or data needed and raise the possibility of losing crucial data. In this scenario, implementing a system or application is critical for improving company processes. The benefits of adopting technology are apparent, including time savings, ease of access to information, cost efficiency, mobility, and many more. However, there are issues such as the time-consuming verification of each staff member's material supply and the administrator's action to respond to each submission since all papers supplied must be evaluated. If any provided information is missing, the administrator must additionally call each staff member. This type of problem emerges when technology is not used in Pusat Pengajian Pengurusan Gunaan (PPPG). Hence, the CEKAP system is a researcher-proposed project to enhance the present system of data collection, evaluation, and endorsement for the PPPG Course File. Aside from that, the goal of this study is to determine the level of acceptability of the CEKAP system among the staff of PPPG. The results of the analysis demonstrate that the suggested system received highly good replies from the respondents. According to the survey, all the elements in the CEKAP system are acceptable and may be used to improve the current system. Consequently, many parties will utilize it to better their performance, resulting in the long-term growth of Malaysia's education business.